Financial Crisis, Taylor Rule and the Fed - Saten Kumar (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2014)
We investigate how the Federal Reserve (Fed) hit the zero lower bound (ZLB) interest rate while operating under a Taylor-type policy rule. We estimate a reaction function and the results indicate that during the crisis Fed increased the weight on output without also increasing the weight on inflation led them to hit the ZLB.
Keywords: 330; Ambiguity; Belief Function; Investment Bubble; Inference